SCOPE AMBIGUITY IN THE JAKARTA POST HEADLINE ARTICLES PUBLISHED IN MAY 2015 - Aulia, Hernita Ratna (LLT Journal: A Journal on Language and Language Teaching, 2017)
As an international language, English has an important role in many aspects of human life. The language has been practically utilized in mass media to provide current information for the people. Printed mass media, as one of the examples, is the topic of this study, newspaper in particular. This study has two purposes, i.e. to find out the scope ambiguity which appears in the articles of the headlines and to analyze the cause of the scope ambiguity. The data of this study are 65 articles taken from the online headlines of The Jakarta Post published in May 2015. The result shows that there are 6 scope ambiguities caused by quantification, 4 scope ambiguities caused by coordination, and 7 scope ambiguities caused by quantification and coordination. Overall, there are 17 scope ambiguities found in The Jakarta Posts headline articles.